Evaluating the Efficiency and Robustness of Beta and Stochastic Discount Factor Methods in Iranian Stock Market - Hossein Talakesh Naeini; Reza Taleblou; Teymor Mohammadi; Parisa Mohajeri (فصلنامه پژوهش‌های اقتصادی ایران, 2022)
Extensive applications of asset pricing in the fields of finance and economics lead to an increasing importance of this issue, which has attracted more attentions of researchers in theoretical and empirical aspects. Due to this issue, the main purpose of this paper is to compare two asset pricing methods i.e. “Beta” and “stochastic discount factor” in Iran Stock Exchange market. Using the monthly data of Tehran Stock Exchange index return and return of shares of the companies listed in the stock exchange market of Iran during 1379(1) to 1398(6), we have formed 5*5 baskets-called 25 portfolios of Fama and French- to evaluate the efficiency and stability of one factor model (capital asset pricing model) and multi-factors model (Fama and French’s 3 factors model) using Generalized Method of Moments (GMM) estimation method. The results show that the aforementioned methods are not completely superior to each other. In fact, for CAPM model, stochastic discount factor method is more efficient and less stable than Beta method and vice versa for Fama and French’s 3 factors model.